2021
DOI: 10.1074/jbc.ra120.015952
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of γ-glutamylmethylamide synthetase provide insight into bacterial metabolism of oceanic monomethylamine

Abstract: Monomethylamine (MMA) is an important climate-active oceanic trace gas and ubiquitous in the oceans. The γ-glutamylmethylamide synthetase (GmaS) catalyzes the conversion of MMA to γ-glutamylmethylamide (GMA), the first step in MMA metabolism in many marine bacteria. The gmaS gene occurs in ~23% of microbial genomes in the surface ocean and is a validated biomarker to detect MMA-utilizing bacteria. However, the catalytic mechanism of GmaS has not been studied due to the lack of structural information. Here, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…NpaA1 shows a similar architecture to GSI protein from Salmonella typhimurium ( St GS) with a 1.2 Å root mean square deviation (RMSD)(Gill & Eisenberg, 2001), and γ-glutamylmethylamide synthetase from Rhodovulum sp. 12E13 ( Rh GmaS) with a 1.0 Å RMSD for the aligned Cα coordinates (Wang et al, 2021). The coordinating residues involved in ATP, glutamate, and Mn 2+ binding are highly conserved between NpaA1 and GS (Figure 4—supplement figure 2A and 2B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…NpaA1 shows a similar architecture to GSI protein from Salmonella typhimurium ( St GS) with a 1.2 Å root mean square deviation (RMSD)(Gill & Eisenberg, 2001), and γ-glutamylmethylamide synthetase from Rhodovulum sp. 12E13 ( Rh GmaS) with a 1.0 Å RMSD for the aligned Cα coordinates (Wang et al, 2021). The coordinating residues involved in ATP, glutamate, and Mn 2+ binding are highly conserved between NpaA1 and GS (Figure 4—supplement figure 2A and 2B).…”
Section: Resultsmentioning
confidence: 99%
“…Docking analysis of NpaA1 and AtdA1 revealed V201 implicated in 1NA binding, in the NpaA1 pocket, leading to a larger naphthylamine-binding volume. In AtdA1, Y205 (conserved in GS proteins) with a larger tryptophan side-chain group may increase steric hindrance for naphthylamine’s diphenyl ring (Murray et al, 2013; Wang et al, 2021). Surprisingly, the V201Y mutant in NpaA1 exhibited higher catalytic activity for both 1NA and aniline compared to the wild-type (Figure 5B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, TMAO in the cells is catabolized to DMA by TMAO demethylase Tdm ( Lidbury et al, 2014 ; Sun et al, 2019 ). With the catalysis of DMA monooxygenase DmmDABC, DMA is further catabolized to MMA ( Lidbury et al, 2017 ; Sun et al, 2019 ), which can be converted to γ-glutamylmethylamide by γ-glutamylmethylamide synthetase GmaS ( Chen Y. et al, 2010 ; Wischer et al, 2015 ; Wang et al, 2021 ). Bioinformatic analysis indicated that tmoXWV homologs are prevalent in SAR11 bacteria ( Lidbury et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%